The Economics of Agricultural Development by John W. Mellor. Ithaca: Cornell University Press, 1966. pp.400. (The Pakistan Development Review, 1968)
The Economics of Agricultural Development is an important book. Throughout the book, Mellor uses economic analysis to organize, extend, understand, and evaluate the economic facts of the agricultural sector in a de¬veloping country. He treats agricultural development within the framework of overall economic growth and highlights the interaction between agriculture and the rest of the economy. ("Agriculture and Foreign Exchange", for instance, is the title of one early chapter, "Agriculture and Capital Formation" is the title of another.) It is not enough, for instance, to show that chemical fertilizer can have significant influence on agricultural output in a developing country. It is also necessary to consider alternative uses of the scarce foreign exchange it requires and alternative uses of industrial capital. Also it is necessary to decide when to stop increasing fertilizer supply and turn to other activities. This essen¬tial integration of agriculture into overall development activity acts as a useful antidote to the special pleading that tends to surround sectoral planning for so large and politically powerful a sector as agriculture and to those economic theorists who ignore this sector, which produces 50-90 per cent of GNP.